Serum associated leucocyte locomotion inhibition and leucocyte motility in malignant melanoma: effect of BCG treatment - Zielinski, C. (1979)
Serum-associated leucocyte locomotion inhibition (SALLI) and leucocyte motility were investigated in patients with malignant melanoma. Ten days after tumour excision twelve out of eighteen patients' sera exhibited a SALLI exceeding the normal range of 15%. The mean SALLI thus reached was 59·2±5·2%. No correlation was observed between SALLI and the level of invasion or the stage of the disease. Six patients selected at random who had a mean SALLI of 71·5±5·8% after tumour excision were further treated by BCG immunotherapy and presented after 8·2±2·9 months of therapy with a significantly (P<0·01) lower SALLI of 32·6±8·1%. In eight patients treated exclusively by surgical excision, SALLI remained basically unchanged in the course of 10±2·8 months (29·0±8·0% vs 30·4±12·9%). The mean index of leucocyte locomotion (LL) of eight melanoma patients who had received BCG for 11·2±2·3 months was 5·9±0·9 cells/field and thus significantly (P<0·01) higher in comparison with the mean index of LL (2·8±0·5) found in eight patients treated by surgical excision only 12·4±2·1 months before testing. In addition, patients receiving BCG had a significantly higher (P<0·05) mean value of LL than fifteen healthy controls who presented with a mean index of LL of 3·4±0·3 cells/field. Our results permit the suggestion that BCG decreases SALLI and increases LL in melanoma patients.